Adult colo-colonic intussusception caused by congenital bands: A case report and literature review. (2016) - Wang, Yifan; Gowing, Stephen; Arena, Goffredo
Highlights: Adult colo-colonic intussusception is predominantly associated with a pathologic lead point. First description of adult colo-colonic intussusception caused by congenital bands. Treatment typically involves en-bloc resection due to concern of malignancy. Laparoscopic techniques are safe, feasible, and may enhance recovery. Abstract: Introduction: Intussusception refers to the telescoping of a segment of bowel into the lumen of an adjacent segment. While pediatric intussusception is common and generally idiopathic, adult intussusception is exceedingly rare and is usually attributable to a pathologic lead point. Presentation of case: 37-year-old man who presented with abdominal pain, and was preoperatively diagnosed with a colo-colonic intussusception. Intraoperatively, the lead point was found to be congenital bands, and there was no evidence of underlying malignancy. He underwent a laparoscopic-assisted extended right hemicolectomy with side-to-side ileo-colic anastomosis. Discussion: Colo-colonic intussusception is a rare cause of intestinal obstruction in adults. Patients generally present with subacute abdominal pain and obstructive symptoms, rendering the clinical diagnosis challenging. Computed tomography has been shown to be the most accurate diagnostic imaging modality. Due to the high incidence of underlying malignancy in adult colo-colonic intussusception, en-bloc resection of the involved bowel segment remains the standard of care. Conclusion: Congenital bands can serve as a lead point in colo-colonic intussusception, particularly in younger adults. Prompt surgical intervention remains paramount to limit morbidity.